An Atypical Syndrome in an Elderly Patient With Systemic Lupus Erythematosus, Sjögren Syndrome, and Primary Biliary Cirrhosis - Xiaojuan SONG,; Xia RONG,; Yi LIU, (Archives of Rheumatology, 2017)
Posterior reversible encephalopathy syndrome is a clinico-radiological syndrome with numerous entities including hypertension, preeclampsia/ eclampsia, renal dysfunction, cytotoxic drugs, systemic infections, and autoimmune diseases. It is a rare happening in patients with autoimmune disease. In this article, we report a case of an elderly female patient having the syndrome, meanwhile, also diagnosed with systemic lupus erythematosus, Sjögren syndrome, and primary biliary cirrhosis.